Composition influence on the microstructures and magnetic properties of FePt thin films - 刘立旺 党红刚 盛伟 王颖 曹江伟 白建民 魏福林 (Chinese physics B, 2013)
The Fex Pt 100x （10nm） （x=31–51） thin films are fabricated on Si （100） substrates by using magnetron sputtering. The highly ordered L1 0 FePt phase is obtained after post-annealing at 700℃in Fe 47 Pt 53 thin film. The sample shows good perpendicular anisotropy with a square loop and a linear loop in the out-of-plane and the in-plane direction, respectively. The variations of the magnetic domains are investigated in the films when the content value of Fe changes from 31% to 51%.